Análisis de los errores en los procesos de inventarios de bodega, monitoreados en el sistema Jd-Edwars en la compañía Agrícola Bancuber S.A. - León Carrasco, Isidro Jonathan (2022)
This final year project includes a case study of the analysis of the most common errors in inventory processes, analyzed in the JD-Edwards system of the agricultural companies Bancuber SA. The main intention of the proposal lies in establishing a theoretical, conceptual, and referential framework, allowing to carry out the measurement of each of the most concurrent errors of the system, through the collection of information using bibliographical, field research, and qualitative and quantitative methods, together with tools such as interviews, surveys, it was possible to define the impact generated by each of the errors, which are the most relevant incidents caused, who causes the incidents, at what level does each incident caused by the mistakes.